Effect of the Initial Rotational and Vibrational State on the Stereodynamics of $N(^4S)+O_2(X^3\sum^-_g)→ O(^3P)+NO(X^2Π)$ Reaction (Journal of Atomic and Molecular Sciences, 2015)
The stereodynamics of the atom-molecule reaction $N(^4S)+O_2(X^3Σ^-_g) → O(^3P)+NO(X^2Π)$ has been studied using quasi-classical trajectory method with the lowest $^2A'$ potential energy surfaces (PESs) given by Sayós et al. [R. Sayós, C. Oliva, M.González, J. Chem. Phys. 117 (2002) 670]. Four generalized polarization-dependentdifferential cross-sections $[(2π/σ) (dσ_{00}/dω_t),$ $(2π/σ)(dσ_{20}/dω_t),$ $(2π/σ)(dσ_{22+}/dω_t),$ $(2π/σ)(dσ_{21-}/dω_t)]$ and distributions $P(θ_r),$ $P(φ_r)$ were calculated. The effects of thedifferent initial rotational and vibrational states were analyzed. It found that the degreeof the forward scatting and the product polarizations show obviously changealong with the initial vibration number, which leads to the increase of alignment anddecrease orientation of product rotational angular momentum $j'.$ Although the influenceof the initial rotational excitation effect on the aligned and oriented distribution ofproduct is not stronger than that of the initial vibration excitation effect, the initial rotationalexcitation makes the alignment of the product rotational angular momentumsmall change in a certain range. Moreover, the $P(θ_r)$ distribution and $P(φ_r)$ distributionchange noticeably by varying the initial vibration number.